Vox Populi or abdication of responsibility?: The influence of the Irish Citizens’ Assembly on the public discourse regarding abortion, 2016-2019 - McNamara, Paul (The Copernicus Journal of Political Studies, 2019)
The last four decades have witnessed enormous changes in the Republic of Ireland in terms of society, economy and politics. Formerly perceived as a poor, peripheral and “priest-ridden” country additionally plagued by political violence in Northern Ireland, over recent decades Irish voters have supported a series of “liberal causes”. Indeed, nowhere is this more apparent than Ireland’s laws concerning abortion, an issue which displayed a seismic shift not only among Irish voters but the political parties which claim to represent them, a shift clearly reflected in the public discourse. At the same time, it will be seen that the use of a Citizens’ Assembly as an exercise in “deliberative democracy” has allowed mainstream political parties to pass responsibility, at least partially, for changes to controversial laws to an extra-parliamentary body, thereby allowing them to claim that they were following the will of “the people” and finally settle one of the longest running conflicts in Irish political life. Thus, this article seeks to examine and describe both how effective the Irish Citizens’ Assembly was at achieving its stated goal and its influence on the nation’s public discourse concerning the issue of abortion.